Increasing the Fuel Efficiency of a Mainline Diesel Locomotive with Separate Section Loading - Riabov, Ye. S.; Yeritsian, B. Kh.; Kolodii, I. M.; Ivanov, S. V.; Sych, O. A.; Halych, A. V. (Science and Transport Progress, 2024)
Purpose. The paper aims to investigate the increase of fuel efficiency of a mainline freight locomotive in the case of separate loading of diesel generators of its individual sections. Methodology. The study was carried out for the non-electrified section between Kharkiv-Sorting and Sumy stations during the movement of a freight train with 45 loaded and empty freight cars in both directions. The movement of a train with a freight mainline two-section diesel locomotive 2TE116 was taken. To determine the parameters of the movement, a mathematical model was developed, which was used to solve a series of traction problems. The traction problems are calculated for the cases of train movement with a series diesel locomotive and a diesel locomotive with separate loading of diesel generators of its individual sections. A method of loading sections is proposed for modeling and the traction characteristics of the locomotive are constructed in accordance with this method. Findings. It has been established that the use of separate loading of diesel generators of individual sections of a diesel locomotive when running a train with loaded cars reduces fuel consumption by 18.7...19.6 % compared to running a serial diesel locomotive. For the case of a train with empty cars, the reduction in fuel consumption is 8.1...10.3 % compared to a train with a serial diesel locomotive. It has been found that the movement of a train with empty cars can be carried out with traction by one section of a diesel locomotive. In this case, the reduction in fuel consumption is 29.5...31.0 %. In all the studied cases, the duration of the movement is practically the same. Originality. The authors of this paper have solved traction problems for a real track section when a train with a freight diesel locomotive is moving, where separate loading of diesel generators of its sections is used. A method for forming the traction characteristics of a locomotive with separate loading of diesel generators is proposed. Practical value. The developed mathematical models of train movement, including for the case of separate loading of diesel generators of diesel locomotive sections, can be used in the modernization of diesel locomotives or the creation of diesel rolling stock using a multi-diesel power plant.